Comparison of Geophysical Methods by Electrical and Electromagnetic Tomography to Determine Water Anomalies, in the Year 2023 - Picado, Victor Rogelio Tirado (European Journal of Applied Sciences, 2024)
The main objective of comparing the methods for carrying out geophysical studies is to establish the benefits of each of them according to their theory, their implementation and action on the geological and soil characteristics. The two geophysical methods were implemented: electrical tomography and electromagnetic geophysical, implemented in the Bonanza area and in Managua, country of Nicaragua. As a result, the assessment, from a scientific point of view, the two methods that were used are suitable to carry out geological soil in any part, the advantages of both methods are the agility and time to obtain the results immediately. It must be considered that the methods must be carried out in the same place and not separately. To have an unbiased evaluation of the methods, they must be carried out under the same geological and soil conditions.